2008
DOI: 10.1007/s00223-007-9084-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone Degeneration and Recovery after Early and Late Bisphosphonate Treatment of Ovariectomized Wistar Rats Assessed by In Vivo Micro-Computed Tomography

Abstract: Bisphosphonates are antiresorptive drugs commonly used to treat osteoporosis. It is not clear, however, what the influence of the time point of treatment is. Recently developed in vivo micro-computed tomographic (CT) scanners offer the possibility to study such effects on bone microstructure in rats. The aim of this study was to determine the influence of early and late zoledronic acid treatment on bone in ovariectomized rats, using in vivo micro-CT. Twenty-nine female Wistar rats were divided into the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
57
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 39 publications
9
57
1
1
Order By: Relevance
“…As such, our study includes novel and relevant information on the effects of a single ZOL injection on trabecular bone microarchitecture and cortical thickness in lumbar as well as in caudal vertebrae. The pattern in bone volume fraction between the four groups in the lumbar vertebrae was exactly the same as that seen in the proximal tibiae [10]. Also, a significant correlation was found between all individual values for bone volume fraction of the lumbar vertebrae and those of the tibiae (r 2 = 0.4, P \ 0.001; data not shown).…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…As such, our study includes novel and relevant information on the effects of a single ZOL injection on trabecular bone microarchitecture and cortical thickness in lumbar as well as in caudal vertebrae. The pattern in bone volume fraction between the four groups in the lumbar vertebrae was exactly the same as that seen in the proximal tibiae [10]. Also, a significant correlation was found between all individual values for bone volume fraction of the lumbar vertebrae and those of the tibiae (r 2 = 0.4, P \ 0.001; data not shown).…”
Section: Discussionsupporting
confidence: 67%
“…Previously, it was shown that 1 year of weekly injections of ZOL inhibited OVX-induced changes in bone microstructure and bone strength of femora and lumbar vertebrae of rats [7][8][9]. Also, in the same rats as used in this study, a single injection of ZOL prevented deterioration of bone microstructure and strength in tibiae of OVX rats for 16 weeks and a single injection at 8 weeks after OVX prevented further deterioration of structure and strength [10]. Additionally, in a dose-response study, it was shown that a single injection can inhibit structural changes seen after OVX in the tibia and retain mechanical properties in the vertebra [12].…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations